Impact of harmonics on tripping time of overcurrent relays - Masoum, Mohammed; Islam, Syed; Tan, Kelvin; Xuan, T. (Curtin University of Technology, 2007)
Theoretical and experimental analyses are used to investigate the effects of harmonics on the operation of overcurrent relays. Two analytical approaches based on relay characteristics provided by the manufacturer and simulations using PSCAD software package are used to estimate tripping times under non-sinusoidal operating conditions. The tests were conducted such that the order and the magnitude of harmonics could be controlled by employing a computer-based single-phase harmonic source. Computed and measured tripping times are compared and suggestions on the application of overcurrent relays in harmonically polluted environments are provided.